A mulher brasileira contemporânea e a maternidade da culpa - Halasi, Fabiana de Souza (2018)
In this study I propose a psychoanalytic reading about motherhood, questioning whether all mothers correspond to social expectations about it. Based on a literature review, I did a deepening in some aspects such as childbirth and breastfeeding, idealization and romanticism and also on the question of guilt. Motherhood as a psychic operation, also implies an option that, in the contemporaneity, suffers social pressure and charges through a pre-established ideal of mother. This makes many women to initiate this process with anticipated guilt. Illustrating this question, I used the free-speech of five celebrities, who have just given birth, points out the super mother must be the full identity of the woman, refractory or not to the ideal of mother. Psychoanalysis places the determinants of the subject beyond the order of the natural, breaking with an instinctive maternal love from the creation of the concept of drive. However this maternal ideal ends up facilitating the guilt and with her, depression. In that process must have a careful look at the woman, because this psychic frame with guilt as background reinforces an ambivalent and alienating behavior. The mother may disinvest in the child by glimpsing other libidinal investments. This kind of attitude alleviates her guilt because a displacement for herself or for what motherhood represents does not mean abandonment or absence of child care. Relativize motherhood with fewer manuals, advice and more respect for individualities and possible mothering is necessary